Sellarsian image- models and Kantian Imagination - Parra Jiménez , Santiago (Con-Textos Kantianos. International Journal of Philosophy, 2023)
It has been assumed by an important element of Kantian scholarship that there is a central connection between the categories and the logical forms of judgement (let us call this the ‘Standard View’ or SV). Although this suggestion is true in a broad sense, it has prevented interpreters from appreciating one fundamental idea of Kant’s theoretical philosophy: that the employment of pure concepts pertains in an equally fundamental way to the unification of sensory material, or what Kant calls the ‘manifold of sense in intuition’, as Wilfrid Sellars has pointed out in his theory of ‘image- models’. We will call this ‘Kantian Intuitionism’, as opposed to the SV. Not only that, this widely held connection of category to judgement has caused what we may call a ‘propositional’ prejudice in contemporary discussions on conceptualism. Specifically, we can appreciate this misconception within the famous Dreyfus- McDowell debate, and their mutual incapacity to account for the Kantian premise that conceptuality suffuses sensory experience without appealing to propositional structures. Parting from Kant’s ‘Clue’ [B104/A79], our contention in this article is that his idea that conceptuality is embedded in both judgmental thought and perception, can be shown to be an appropriate answer to the Standard View, and furthermore, to constitute a starting point to enlarge the comprehension of some doctrines of Kantian theoretical philosophy. Among these, the Transcendental Deduction and the Schematism. In this sense, our reading will show the broad implications of the ‘Clue’, not only for the comprehension of Kant, but also for the clarification of some contemporary philosophical discussions.